Regional Development Planning of Participatory in to Colaborative Governance Perspective at Bima Municipality West Nusa Tenggara Province - Muhammad Hasyim; Muchlis Hamdi; Muh Ilham; Mansyur Mansyur (Budapest International Research and Critics University, 2022)
This study aims to find out and analyze the formation of participatory regional development planning policies in the Municipality of Bima in the perspective of collaborative governance while at the same time finding new models or concepts in the formation of development planning policies in the Municipality of Bima in the perspective of collaborative governance to make it more participatory. Participatory regional development planning is a spirit transmitted by the central government through the implementation of regional autonomy as a form of government responsibility in increasing public political participation, capturing community aspirations and increasing the degree of democratization in state management. This study uses a qualitative research method with an exploratory descriptive approach and uses an all-systems thinking approach through the learning process, namely Soft System Methodology (SSM). The results of this study indicate that the formulation of regional development planning policies in Bima Municipality from the point of view of the concept of collaborative governance does not yet reflect a participatory policy formation process. The dynamics of collaboration which is the core of participatory in principled engagement has not been effective because the government's role is still very dominant. The implication is that shared motivation has not been properly structured and finally the capacity for joint action that reflects the unification of all resources as a participatory spirit has not occurred.